Contrast-associated acute kidney injury following peripheral angiography. Issue 6 (2nd November 2021) - Woltemath, Alyssa A.; Gonzalez, Gabriel; Tecson, Kristen M.; Vasquez, Javier
Abstract: Contrast-associated acute kidney injury (CA-AKI) is a well-known complication following angiography. Peripheral angiograms have been delayed or canceled for fear of worsening renal function leading to dialysis dependence. With the emergence of preventive measures, it is hypothesized that the risk of CA-AKI may be lower than previously observed. We performed a retrospective chart review of a single surgeon's 118 cases who underwent angiographic procedures from September 2019 through August 2020, recording patient characteristics and serum creatinine values. This cohort was comprised of 65 (55%) men and had a median age of 69 years [quartile 1 = 60, quartile 3 = 75]; 55 (47%) had diabetes mellitus and the median estimated glomerular filtration rate was 64 [45, 84] mL/min/1.73 m 2 . We observed a statistically significant decrease in paired serum creatinine (-0.02 mg/dL) following the procedure, and only 4 patients (3.4%) developed CA-AKI, with older age and elevated baseline creatinine being associated with reduced kidney function. We did not detect an adverse relationship between contrast volume and CA-AKI. While CA-AKI continues to be a concern for patients who require peripheral angiographic procedures, this study found the overall risk to be low. This may be partly attributable to the use of pre- and postprocedure hydration protocols and lower contrast volumes.